On the Political Economy of Solar Radiation Management - Ott, Konrad K. (Frontiers in Environmental Science, 2018)
The paper investigates what kind of economic system would favor research and deployment of Solar Radiation Management (SRM), especially sulfur based stratospheric aerosol injection (SAI). The political economy argument combines moral, economic, and political assumptions in order to reach a credible “fitting”-judgement. After presenting some normative ideas on climate ethics, the concept of political economy (PE) is explained. Variants of capitalism are distinguished. These considerations are substantiated by investigating the relation between the U.S. economic system and recent support for SRM, especially for SAI. The paper concludes that the U.S. economic system has strong affinities to SRM supported by an emerging agency network that tries to establish a pro-SRM narrative and launch SAI research initiatives. There is recent evidence that SRM has found support from policy makers. To supporters of “green” variants of capitalism, the main claims of the article provide reasons against SAI-research. The article finishes with some remarks why SAI-research should be conditional.